Natural Language Processing Fundamentals Build Intelligent Applications That Can Interpret the Human Language to Deliver Impactful Results. - Ghosh, Sohom (Packt Publishing Ltd, 2019)
Natural Language Processing Fundamentals starts with basics and goes on to explain various NLP tools and techniques that equip you with all that you need to solve common business problems for processing text.